The Role of a Leader and the Development of Leadership Skills in the Period of Digital Transformation ("Journal "U". Economy. Management. Finance.", 2021)
The use of modern innovative technologies in the business processes of organizations requires constant improvement of personal and professional qualities not only on the part of the management, but also on the part of the company's personnel. In the period of global digitalization, to improve the career path of a specialist, employees must have formed leadership qualities. Despite the fact that the key qualities of a leader remain unchanged for a long time, an innovative approach has made its own adjustments.
Keywords: leader; leadership qualities; leadership development; digitalization; digital transformation